2017
DOI: 10.1016/j.rce.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Implicación de la congestión venosa sistémica en la insuficiencia cardíaca

Abstract: Systemic venous congestion has gained significant importance in the interpretation of the pathophysiology of acute heart failure, especially in the development of renal function impairment during exacerbations. In this study, we review the concept, clinical characterisation and identification of venous congestion. We update current knowledge on its importance in the pathophysiology of acute heart failure and its involvement in the prognosis. We pay special attention to the relationship between abdominal conges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Cardiac filling pressures increase due to ventricular interdependence or due to chronically elevated left-sided filling pressures transmitted back through the pulmonary system into the right ventricle [5], resulting in systemic congestion. The excessive fluid is stored in the splanchnic venous system, which contains highly compliant capacitance veins that can store up to 65% of the total blood volume without repercussions on system hemodynamics [7,8]. In an attempt to increase the effective circulatory volume, sympathetic stimulation induces vasoconstriction of the splanchnic capacitance vessels and vasodilation of the hepatic veins [9].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac filling pressures increase due to ventricular interdependence or due to chronically elevated left-sided filling pressures transmitted back through the pulmonary system into the right ventricle [5], resulting in systemic congestion. The excessive fluid is stored in the splanchnic venous system, which contains highly compliant capacitance veins that can store up to 65% of the total blood volume without repercussions on system hemodynamics [7,8]. In an attempt to increase the effective circulatory volume, sympathetic stimulation induces vasoconstriction of the splanchnic capacitance vessels and vasodilation of the hepatic veins [9].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the appetite assessment was undergone by SNAQ and showed that appetite loss was commonly seen in patients with CHF. In addition to the abnormality of cardiac and pulmonary function, the congestion of CHF may also cause the functional change in other organs, including liver, kidney, brain and gastrointestinal tract, which probably causes the appetite loss [ 30 ]. However, the relationship between CHF and pancreatic function is rarely reported.…”
Section: Discussionmentioning
confidence: 99%